Demographic features of two cohorts of tadpoles of the Lesser Snouted Treefrog (Scinax nasicus) - Gómez, Valeria Isabel (2023)
I studied the population dynamics in two Scinax nasicus tadpole under natural conditions. From several samples collected during the larval cycle, I assembled different ecological data and a survivorship table. Main results included: (1) The mean time until metamorphosis was 19.9 days. (2) Tadpoles remained at Gosner Stages 29–31 and 32–34 for the least amount of time. (3) Tadpoles stayed at Stages 26–28 for the longest duration. (4) Average life expectancy for a newly hatched tadpole was 7.3 days. (5) The survivorship curve was most similar to a Type II curve. The population dynamics of S. nasicus tadpoles were mainly influenced by predation pressure.